Fine-mapping of lipid regions in global populations discovers ethnic-specific signals and refines previously identified lipid loci. (25th November 2016) - Zubair, Niha; Graff, Mariaelisa; Luis Ambite, Jose; Bush, William S.; Kichaev, Gleb; Lu, Yingchang; Manichaikul, Ani; Sheu, Wayne H-H.; Absher, Devin; Assimes, Themistocles L.; Bielinski, Suzette J.; Bottinger, Erwin P.; et al.
Abstract: Genome-wide association studies have identified over 150 loci associated with lipid traits, however, no large-scale studies exist for Hispanics and other minority populations. Additionally, the genetic architecture of lipid-influencing loci remains largely unknown. We performed one of the most racially/ethnically diverse fine-mapping genetic studies of HDL-C, LDL-C, and triglycerides to-date using SNPs on the MetaboChip array on 54, 119 individuals: 21, 304 African Americans, 19, 829 Hispanic Americans, 12, 456 Asians, and 530 American Indians. The majority of signals found in these groups generalize to European Americans. While we uncovered signals unique to racial/ethnic populations, we also observed systematically consistent lipid associations across these groups. In African Americans, we identified three novel signals associated with HDL-C ( LPL, APOA5, LCAT ) and two associated with LDL-C ( ABCG8, DHODH ). In addition, using this population, we refined the location for 16 out of the 58 known MetaboChip lipid loci. These results can guide tailored screening efforts, reveal population-specific responses to lipid-lowering medications, and aid in the development of new targeted drug therapies.